Development and Psychometric Testing of a New Short-Form of the Premenstrual Symptoms Questionnaire (PSQ-S) - Takeda T; Yoshimi K; Kai S; Inoue F (Dove Medical Press, 2022)
Takashi Takeda, Kana Yoshimi, Sayaka Kai, Fumi Inoue Research Institute of Traditional Asian Medicine, Kindai University, Osaka-Sayama, JapanCorrespondence: Takashi Takeda, Research Institute of Traditional Asian Medicine, Kindai University, Osaka-Sayama, Japan, Tel +81-72-366-0221 (Ext. 3393), Fax +81-72-366-6661, Email take@med.kindai.ac.jpPurpose: The Premenstrual Symptoms Questionnaire (PSQ) is a patient-reported outcome measurement tool for premenstrual symptoms. Although the PSQ is a very useful tool with 14 items to screen for a wide variety of premenstrual symptoms, not everyone will respond to all the questions. Fewer questions would be less burdensome on the respondents. We aimed to develop and analyze the psychometric properties of a short-form of the PSQ (PSQ-S).Patients and Methods: The study participants were from an earlier study with a sample of 1388 female students. We reanalyzed data collected from 922 students with regular menstrual cycles who completed the PSQ, premenstrual dysphoric disorder (PMDD) scale, Somatic Symptom Scale-8 (SSS-8), and numerical rating scale (NRS) for menstrual pain. First, we selected nine items for the PSQ-S based on the results of the corrected item-total correlation analysis. The PSQ-S was then analyzed for reliability and validity using the classical test theory. Moreover, item response theory was applied to test the psychometric properties of the PSQ-S.Results: Cronbach's α for the PSQ-S score was 0.93. Principal component factor analysis revealed a one-factor model. Confirmatory factor analysis showed that the one-factor model was a good fit. The PSQ-S total score was strongly correlated with the PSQ total score, PMDD scale score, and SSS-8 score (r=0.978, 0.854, and 0.648, respectively) and moderately correlated with the NRS (r=0.437). Item response theory analyses showed that the constructs and items of the PSQ-S had satisfactory discrimination, difficulty parameters, item information curves, and test information curves. Receiver operating characteristic curve analysis revealed a cut-off score of ≥ 22 for suspected premenstrual disorders based on the total PSQ-S score.Conclusion: The PSQ-S, consisting of nine items from the PSQ, had sufficient reliability and validity and could be a convenient assessment tool for premenstrual symptoms in routine clinical practice.Keywords: menstruation, premenstrual disorders, validity testing, item response theory